2009
DOI: 10.1007/s10162-009-0158-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FDA-Approved Drugs and Bioactives that Protect Hair Cells in the Zebrafish (Danio rerio) Lateral Line and Mouse (Mus musculus) Utricle

Abstract: The hair cells of the larval zebrafish lateral line provide a useful preparation in which to study hair cell death and to screen for genes and small molecules that modulate hair cell toxicity. We recently reported preliminary results from screening a small-molecule library for compounds that inhibit aminoglycoside-induced hair cell death. To potentially reduce the time required for development of drugs and drug combinations that can be clinically useful, we screened a library of 1,040 FDA-approved drugs and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
107
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(111 citation statements)
references
References 48 publications
4
107
0
Order By: Relevance
“…Notably, not all early endocytic routes employ Rab5 (49), including routes that Using this technique, it is straightforward to quantitatively evaluate whether other compounds previously shown to protect HCs from AG exposure affect AG loading. Many such compounds have been identified in LL zebrafish screens (42)(43)(44). Here we show results for benzamil, raloxifene, ractopamine, and dynasore.…”
Section: Resultsmentioning
confidence: 74%
“…Notably, not all early endocytic routes employ Rab5 (49), including routes that Using this technique, it is straightforward to quantitatively evaluate whether other compounds previously shown to protect HCs from AG exposure affect AG loading. Many such compounds have been identified in LL zebrafish screens (42)(43)(44). Here we show results for benzamil, raloxifene, ractopamine, and dynasore.…”
Section: Resultsmentioning
confidence: 74%
“…In sponges, primary cilia label with FM 1-43, a steryl dye, and also with a conjugate to the antibiotic neomycin sulphate, both non-specific calcium channel blockers (Ludeman et al, 2014;Fig. 2E,F), as do primary cilia in the lateral line of fish and inner-ear hair cells (Ou et al, 2009). The cilium is non motile and lacks a central pair of microtubules (Ludeman et al, 2014;Fig.…”
Section: Sensory Cilia In the Osculummentioning
confidence: 99%
“…Once inside the hair cell, the aminoglycosides cause increases in reactive free radicals and mitochondrial calcium concentration, leading to either apoptosis or necrosis (1,2,15). While there are many points at which aminoglycoside-induced hair cell death could be prevented, blocking ototoxin entry into hair cells may be the most effective strategy for protection (10,16).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies (16)(17)(18)(19)(20)(21)(22)(23) have shown that the lateral line system of zebrafish larvae is a powerful model for discovering compounds that can protect sensory hair cells from the toxic side effects of aminoglycoside antibiotics. At least 24 compounds have been described that protect zebrafish lateral line hair cells, some of which (16,20,23) reduce or block the uptake of Texas red-conjugated gentamicin (GTTR) into Aminoglycoside antibiotics are used to treat life-threatening bacterial infections but can cause deafness due to hair cell death in the inner ear.…”
Section: Introductionmentioning
confidence: 99%